Lexical Cohesion through Repetition in Three Selected Poems from the Anthology ”Aku Ingin Jadi Peluru” by Widji Thukul - Yamjirin, Abdussalam Jabaruddin; Winarni, Efid; Sumarlam, Sumarlam (Journal of Language Education Studies and Applied Linguistics, 2025)
This study examines lexical cohesion through repetition in three selected poems from the anthology Aku Ingin Jadi Peluru by Widji Thukul. The aim is to identify the types, functions, and meanings of repetition as linguistic and rhetorical tools for conveying ideological messages and emotional expressions. Using a descriptive qualitative approach, data were collected through observation and note-taking techniques and analyzed using the distributional method with the Immediate Constituent (IC) technique. The findings reveal three primary types of repetition: anaphora (28.57%), which emphasizes themes and personal reflection; mesodiplosis (14.29%), which highlights irony and alienation; and full repetition (57.14%), which reflects the poet's struggles and existential anxieties. These results demonstrate that repetition in Widji Thukul's poetry serves not only aesthetic purposes but also functions as a strategic tool for social critique and identity exploration. This study contributes to the field of lexical cohesion in Indonesian poetry and provides a foundation for further research on cohesion in other literary works.